2020
DOI: 10.3390/bdcc4020008
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence-Enhanced Predictive Insights for Advancing Financial Inclusion: A Human-Centric AI-Thinking Approach

Abstract: According to the World Bank, a key factor to poverty reduction and improving prosperity is financial inclusion. Financial service providers (FSPs) offering financially-inclusive solutions need to understand how to approach the underserved successfully. The application of artificial intelligence (AI) on legacy data can help FSPs to anticipate how prospective customers may respond when they are approached. However, it remains challenging for FSPs who are not well-versed in computer programming to implement AI pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…To build safer, future-proof food protection technologies, food researchers and policymakers who are not computer scientists can leverage AI to support decision-making to design better food security systems that are future-ready. The current paper contributes significantly to the extant literature by providing a user-friendly approach so that AI usage is democratized [60,61]. This allows novice AI users to perform research analysis using probabilistic reasoning using BN.…”
Section: Discussionmentioning
confidence: 99%
“…To build safer, future-proof food protection technologies, food researchers and policymakers who are not computer scientists can leverage AI to support decision-making to design better food security systems that are future-ready. The current paper contributes significantly to the extant literature by providing a user-friendly approach so that AI usage is democratized [60,61]. This allows novice AI users to perform research analysis using probabilistic reasoning using BN.…”
Section: Discussionmentioning
confidence: 99%
“…Access to finance, according to How et al [13], is a crucial factor in poverty alleviation, but financial institutions must know how to target the neglected effectively.…”
Section: Introductionmentioning
confidence: 99%
“…How et al [13] went on to say that using artificial intelligence (AI) for data records can assist financial institutions in predicting how prospective clients will react when contacted. However, how et al [13] suggested that implementing AI projects for financial service providers who are not computer programmers remains difficult.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations